The Rhetoric of Widening Participation in Higher Education and its Impact Ending the Barriers against Disabled People - Kikabhai, Navin (Springer International Publishing, 2018)
This book offers a critical investigation of the exclusion of individuals described as having 'learning difficulties' from participation in higher education. Using a postmodernist framework, the author explores the insights and experiences of a theatre group attempting to develop an undergraduate degree programme in the performing arts. In doing so, he provides a theoretical map of insights into discourses of power and knowledge, and makes transparent competing and contradictory discursive practices. Suggesting that 'learning difficulties' is a constructed and re-constructed discourse serving normative interests, the author demonstrates that despite the rhetoric of widening participation, individuals are intentionally beset by barriers, silenced and excluded from degree level participation. The author calls for a radical re-think of the notion of 'learning difficulties', segregated provision, access to employment in theatre, and critically questions the notion of participation in higher education. This pioneering volume will appeal to students and scholars of inclusive education, (critical) disability studies, cultural studies and the sociology of education.